Cholecystectomy after endoscopic sphincterotomy in elderly: A dilemma: Cholecystectomy in geriatric age - Baykan, Ahmed Ramiz; Cerrah, Serkan; Ogul, Levent; Temiz, Ayetullah; Kasap, Elmas (Journal of Surgery and Medicine, 2022)
Background/Aim: Although cholecystectomy is recommended by many guidelines after endoscopic retrograde cholangiopancreatography (ERCP) for gallstones, the necessity of cholecystectomy in geriatric patients is a matter of debate. Here we compare the outcomes of new biliary events in cholecystectomized and non-cholecystectomized patients of geriatric age after ERCP for suspected choledocholithiasis. Methods: Non-cholecystectomized patients who underwent ERCP for choledocholithiasis from 2015 to 2017 were included in this retrospective cohort study. Patients with other biliary pathologies, incomplete clearance of common bile duct stones, and those who could not be reached at follow-up were excluded from the study. Biliary events (cholecystitis, cholangitis, pancreatitis, re-ERCP) were evaluated by considering age groups in patients with and without cholecystectomy in their follow-up after sphincterotomy. Results: A total of 284 patients were followed for an average of 69.77 (0.2) months. The cumulative incidence of biliary events in cholecystectomized patients was lower (16% vs. 21.5%; P < 0.001), and cholecystectomized patients had a longer time to the occurrence of events (mean 74.49 [0.27] months vs. 73.50 [0.33] months; P = 0.03). There was no significant difference in the frequency of biliary events between elderly patients with and without cholecystectomy (P = 0.81), and the cumulative incidence of biliary events in the in situ group was significantly lower than that in the geriatric group (17.5% vs 32.6%; P = 0.03) Conclusion: Although cholecystectomy significantly reduces subsequent biliary complications in young patients, it does not provide a statistically significant benefit in geriatric patients. We believe that there may be no need for routine prophylactic cholecystectomy after endoscopic sphincterotomy in geriatric patients.